Brain Abscesses Due To Listeria Monocytognes: Case Report - Midi, İpek; Ekinci, Günseli; Yaroğlu, Selcen; Aktan, Sevinç (Fırat University, 2005)
Meningitis is clinically the most common manifestation of Listeria monocytogenes central nervous system infection, while brain abscess occurs in about 1% of patients. Brain abscesses are usually located supratentorial and also infrequently infratentorial especially brain system. Corticosteroids in particular are significant predisposing factors in patients with two or more brain abscesses. Mortality resulting from listerial brain abscess, whether solitary or multiple, is nearly three times higher than nonlisterial brain abscess, probably in part because of both underlying diseases and immunosuppressive therapy. Early diagnosis and treatment for central nervous system involment with listeria are important factors for the prognosis of illness. 52 year-old man was admitted to hospital with neck stiffness and unconsciousness. He was using high dosage prednisolone for the diagnosis of interstisial pnemonia. Listeria monocytogenes menengitis and bacteremia were found out in serological and liquor tests. During the clinical course, focal neurological deficit developed and cranial MR imaging showed brain abscesses in the localisation of pons and cerebellum. Despite the the effective treatment with antibiotics, the patient died within 32 days.

Listeria monositogeneze bağlı santral sinir sistemi enfeksiyonu en sık olarak menenjitle kendini göstermektedir. Bu olguların %1’inde listeriaya bağlı beyin absesi gelişimide mevcuttur. Apselerin yerleşimi supratentorial olabileceği gibi nadir de olsa infratentorial bölgede özellikle beyin sapında görülmektedir. Tek veya multiple beyin absesi olanlarda kortikosteroidler predispozan faktör olarak bildirilmektedir. Listeriaya bağlı beyin abselerinde mortalite altta yatan hastalık ve immunosupresif tedaviye bağlı olarak non-listerial abselere oranla üç kat daha fazla olmaktadır. Listeria monositogeneze bağlı santral sinir sistemi tutulumlarında erken tanı ve tedaviye başlanması hastalığın prognozu açısından önem taşımaktadır. Bu çalışmada intersitisyel pnömoni nedeni ile yüksek dozde prednol tedavisi alırken, ateş, bilinç bulanıklığı, ense sertliği gelişen 56 yaşındaki erkek hastada Listeria monositogenez menenjiti ve bakteriyemisi saptanmış, klinik izlem sırasında fokal nörolojik muayene bulgularının ortaya çıkması üzerine çekilen kranial MR incelemesinde pons ve serebellumda listeriaya bağlı abse tesbit edilmiştir. Ancak antibiyotik tedavisine rağmen hasta kaybedilmiştir.
Listeria Monositogeneze Bağlı Beyin Absesi: Olgu Sunumu